PHOTODYNAMIC THERAPY FOR EXTRAFOVEOLAR CHOROIDAL OSTEOMA. Issue 5 (May 2020) - Mazloumi, Mehdi; Dalvin, Lauren A.; Ancona-Lezama, David; Mashayekhi, Arman; Shields, Carol L.
Abstract : Purpose: To evaluate the outcome of photodynamic therapy (PDT) in the management of extrafoveolar choroidal osteoma. Methods: The authors performed a retrospective chart review of all patients with choroidal osteoma that did not involve the foveola and were treated with standard-fluence PDT. Results: Nine eyes with extrafoveolar choroidal osteoma were studied. Mean logarithm of the minimum angle of resolution best-corrected visual acuity at initial examination was 0.07 (Snellen ∼20/25). The osteoma was treated with 1 (8/9) or 2 (1/9) PDT sessions using 50 J/cm 2 . After a mean follow-up of 49 months, the treated area of osteoma demonstrated complete (4/9) or partial (5/9) regression, with a mean of 73% regression in the PDT-treated areas. Tumor growth in the region of PDT was noted in 3 cases (3/9) (one tumor toward the foveola and two tumors at the margin away from the foveola), but in no case did the tumor reach the foveola. Therefore, PDT controlled tumor growth in 8 of 9 cases with only 1 of 9 cases showing growth through the PDT scar into foveola. Mean logarithm of the minimum angle of resolution visual acuity at last follow-up was 0.04 (Snellen ∼20/20) ( P = 0.59). Conclusion: Photodynamic therapy is an effective modality for the management of extrafoveolar choroidal osteoma, minimizing tumor growth toward the foveola and preserving visual acuity. Abstract : Photodynamic therapy was effective in the prevention of tumor growth toward the foveola and in preservation of visual acuity in eight of nine eyes with vision-threatening extrafoveolar choroidal osteoma.